2015
DOI: 10.5897/ajar2013.8022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of planting space on plant population at harvest and tuber yield in taro (Colocasia esculenta L).

Abstract: A two year study was carried out in two locations in south eastern Nigeria in the years 2008 and 2009, to determine the effect of planting space on plant population at harvest, and corm yield in cocoyam cultivars. This was aimed to identify optimum planting space for optimum cocoyam production. Five taro cultivars; Nkpong, Ugwuta, Nworoko, Odogolo and Nadu were used. Three planting space; 50 x 100 cm, 40 x 100 cm and 30 x 100 cm were tested. The result showed that decreasing planting space from 50 x 100 cm to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Similarly, studies by Lu et al (2001) on taro, Khan et al (2003) on some potato (Solanum tuberosum) cultivars and Scheffer et al (2005) on Japanese taro indicated that there was a strong and positive association between weight of corms and tubers on water availability and temperature, which was directly related to planting date. The variation in yield and yield attributes seen among accessions in the present work corroborates the findings of Ogbonna et al (2015) in their studies on Nigerian taro.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, studies by Lu et al (2001) on taro, Khan et al (2003) on some potato (Solanum tuberosum) cultivars and Scheffer et al (2005) on Japanese taro indicated that there was a strong and positive association between weight of corms and tubers on water availability and temperature, which was directly related to planting date. The variation in yield and yield attributes seen among accessions in the present work corroborates the findings of Ogbonna et al (2015) in their studies on Nigerian taro.…”
Section: Discussionsupporting
confidence: 91%
“…This also related to the overall issue of plant density and therefore seeding rate and seed placement. Optimum planting depends on its effect on seed yield and quality in many crops (Ogbonna et al, 2015;da Silva et al, 2016;Abu and Odo, 2017;Ngozi and Chidera 2017). Row planting has an advantage particularly with tussock grasses, such as Panicum, Andropogon, Pennisetum and Setaria species and seed production of Cenchrus spp.…”
Section: Influence Of Row Spacingmentioning
confidence: 99%
“…However, it did not occur on taro plants in this experiment. It seems that at higher plant density taro experienced self-sucker (Ogbonna et al, 2015), so that plant population is not increase with increasing plant density.…”
Section: Leaf Area and Net Assimilation Rate (Nar)mentioning
confidence: 99%
“…Liou (1984) observed that increasing plant population from 26,600-83,300 plants haG 1 increased corm yield from 17-56 t haG 1 . However, to minimize plant competition, improving plant population should be followed by plant arrangement (Ogbonna et al, 2015). With plant spacing of: 50×100, 40×100 and 30×100 cm, Ogbonna et al (2015) found that increasing plant population from 20,000 plants haG 1 (plant spacing of 50×100 cm) to 25,000 plants haG 1 (plant spacing of 40×100 cm) resulted an increase in plant population at harvest but there was a decline in plant population for further decreased in plant spacing (30×100 cm).…”
Section: Introductionmentioning
confidence: 99%